Implementasi Model Transportasi Untuk Optimalisasi Biaya Distribusi Air Mineral Aqua Di Pt Tirta Utama Abadi Kabupaten Bandung - Aas Widia; Bangkit Nuratri (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Product distribution is one of the key activities in a company’s operations because it is directly related to cost efficiency and the smooth delivery of products to their destinations. A distribution system that has not been optimally planned can lead to inefficient operational costs. This issue also occurs in the distribution process of Aqua mineral water at PT Tirta Utama Abadi in Bandung Regency, which is still carried out conventionally, resulting in delivery allocations that do not optimally consider cost efficiency. This study employs a descriptive quantitative approach by applying transportation models, namely Vogel’s Approximation Method (VAM) to obtain the initial solution and the Modified Distribution Method (MODI) to test the optimality of the solution. The research data include supply capacity from two warehouses, demand from three distribution areas, and transportation costs for the period from November to December 2025. The results of the analysis show that the application of the transportation model is able to produce a more efficient distribution pattern compared to the previous system. Distribution costs in November 2025, which were originally Rp21,794,083, were reduced to Rp19,331,108, resulting in savings of Rp2,462,975 (11.30%). Meanwhile, in December 2025, distribution costs of Rp20,803,010 were reduced to Rp17,640,728, resulting in savings of Rp3,162,282 (15.20%). Thus, the implementation of the transportation model can serve as an alternative approach to improving the efficiency of the company’s distribution costs.